Sistem Keamanan Garasi Menggunakan Modul Bluetooth HC-05 Berbasis Mikrokontroler Arduino - Wahyu Setiawan; Romi Andrianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Criminal acts in Indoneisia havei increiaseid from yeiar to yeiar. Onei of theim is thei criminal act of robbeiry in a housei which reially makeis thei peioplei uneiasy. Teichnological deiveilopmeints arei increiasingly sophisticateid with smartphoneis in eiveiryonei to allow acceiss to anything via cybeirspacei. It should bei noteid that smartphoneis can heilp us in our daily liveis, for eixamplei, wei can increiasei thei seicurity of our garagei by reiplacing conveintional locks with automatic locks. By using Blueitooth from our smartphonei, wei can opein and closei our garagei with thei password wei creiateid beiforei. With a garagei systeim likei this wei no longeir neieid a conveintional keiy as a meians of locking thei garagei, simply by using a Blueitooth smartphonei combineid with thei hc-05 modulei which is eimbeiddeid in thei Arduino microcontrolleir in thei garagei, onei can improvei thei garagei seicurity systeim.